Hospital-at-home care in Singapore: A review of overseas protocols and guidelines to support implementation and policy redesign (systematic review). - Clive Goh; Jun Jie Soh; Valerie Ng; Yi Feng Lai (PLoS ONE)
Objective Hospital-at-Home (HaH) is a care model providing acute, hospital-level care to patients in their own homes. It is gaining traction worldwide and could become an integral part of standard healthcare in the future. However, for countries like Singapore, implementation inefficiencies prevent the optimal uptake and establishment of HaH. Currently, there are no standardised guidelines guiding healthcare providers on effective implementation. Thus, our objective is to distil information from existing guidelines worldwide to collate the best practices for HaH implementation. Methods The systematic review is according to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 checklist. A literature review across three databases and an Advanced Internet Search was performed to collect guidelines that included recommendations on HaH implementation requirements. Two authors independently extracted recommendations. Two reviewers independently assessed guideline quality using the Appraisal of Guidelines for Research and Evaluation II Instrument (AGREE II), which consisted of twenty-three items across six domains. Overall guideline quality was calculated as the total points from all six domains as a percentage over maximum points, and guidelines with overall scores of 50% or more were deemed high quality. Results Fourteen guidelines and seven sections were identified, which covered the following topics: inclusion & exclusion criteria, admission process, clinical handover, discharge, team structure, partnerships with external stakeholders, and medication administration. Key observations underline deficiencies in addressing staff safety, appropriate medical supply storage, and admission after hours. The main discrepant recommendations included self-discharge, team structure, partnerships with primary care providers, and medication self-administration. Methodological quality of guidelines varied, with overall AGREE II scores ranging from 38.5% to 58.4%. Individual domain scores were consistently low for Rigour of Development and Editorial Independence. Despite low scores in these domains, all fourteen guidelines were deemed appropriate for information extraction. Conclusion Despite inconsistencies among guidelines, a set of streamlined recommendations were consolidated. In Singapore, addressing home environment constraints, fostering stronger partnerships with community providers, and leveraging on multidisciplinary care can enhance the feasibility and sustainability of these HaH recommendations. Policy redesign should focus on further stratifying patients based on home suitability, leveraging on technology to support clinical handovers or collaborations, and investing in multidisciplinary training to strengthen workforce capabilities. In all, healthcare providers around the world should consider contextualising these recommendations within local socioeconomic and healthcare contexts for optimal HaH implementation.